2021
DOI: 10.1002/dad2.12150
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of preclinical Alzheimer's disease biomarker results in research and clinical settings: Why, how, and what we still need to know

Abstract: Disclosure of personal disease‐related information to asymptomatic adults has been debated over the last century in medicine and research. Recently, Alzheimer's disease (AD) has been conceptualized as a continuum that begins with a “preclinical” stage in which biomarkers are present in the absence of cognitive impairment. Studies have begun assessing the safety, psychological, and behavioral effects of disclosing both AD‐related genetic and biomarker information to cognitively unimpaired older adults. Yet, deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 47 publications
2
47
0
Order By: Relevance
“…Prior studies have examined the effects of disclosing AD dementia risk to cognitively unimpaired persons and also to care partners of adults with mild cognitive impairment (MCI). 22,23 This study is the first to examine how such disclosure affects cognitively unimpaired persons' family members and friends; we find important parallels with past research. Our results suggest that, if adults with preclinical AD become "patients-in-waiting," their family members become "pre-caregivers," offering support in the present and anticipating future care responsibilities.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Prior studies have examined the effects of disclosing AD dementia risk to cognitively unimpaired persons and also to care partners of adults with mild cognitive impairment (MCI). 22,23 This study is the first to examine how such disclosure affects cognitively unimpaired persons' family members and friends; we find important parallels with past research. Our results suggest that, if adults with preclinical AD become "patients-in-waiting," their family members become "pre-caregivers," offering support in the present and anticipating future care responsibilities.…”
Section: Discussionsupporting
confidence: 63%
“…Prior studies have examined the effects of disclosing AD dementia risk to cognitively unimpaired persons and also to care partners of adults with mild cognitive impairment (MCI) 22,23 . This study is the first to examine how such disclosure affects cognitively unimpaired persons' family members and friends; we find important parallels with past research.…”
Section: Discussionmentioning
confidence: 54%
“…This was somewhat surprising for the strategy focused on study benefits, given that we expected participants with dementia to differentially benefit from tactics that offer social support services and make study test results such as routine laboratories, neuropsychological measures, and biomarker results more accessible to them and their families. A possible explanation for the lack of interaction is that these benefits were viewed as universally important to participants, regardless of their diagnostic category [ 27 ]. Alternatively, some of the tactics with the greatest potential for effect modification (e.g., access to a clinical care or a social worker) were employed by a very small number of ADRCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although inherited susceptibility is beyond the scope of our review, extensive research on the impact of revealing an increased probability [50-57] or absolute certainty [58-60] of developing dementia has demonstrated that catastrophic outcomes are rare, knowledge of the test results does not affect cognition and participants also perceive benefits. So far, evidence on disclosing biomarkers information is limited, but the few available studies suggest it is safe and actionable [61-66]. However, stigmatization and discrimination are concerns that need further scrutiny [67, 68].…”
Section: Discussionmentioning
confidence: 99%